HUBUNGAN ANTARA OPTIMISME DENGAN ADAPTABILITAS KARIR PADA MAHASISWA GENERASI Z - Isma Shafira Putri; Reny Yuniasanti (Fakultas Psikologi Universitas Tarumanagara, 2023)
This study aims to determine the relationship between optimism and career adaptability in Generation Z students. There were 102 subjects in the study with the criteria of active students, aged 18- 22 years selected using purposive sampling method. Two scales used in this research were the Career Adapt-Adaptability Scale (CAAS) and the optimism scale. Data analyzed using Pearson product-moment shows a significant positive correlation between optimism and career adaptability among Generation Z students (r =0.553 p < 0.001). The coefficient of determination (R2) is 0.306, indicating that the optimism variable contributes a 30.6% variance in career adaptability. Therefore, higher education needs to foster optimism in students to improve their adaptation to changing circumstances that may affect their future careers.